Effect of Estrogen Receptor on the Relationship Between HER2 Immunohistochemistry Score and Pathological Complete Response to Neoadjuvant Treatment in HER2-Positive Breast Cancer - Miaomiao Jia; Haibo Yang; Lihui Pan; Jinnan Gao; Fan Guo (The Breast Journal)
Conclusion: HER2 IHC 2+ may indicate a decreased tpCR rate, bpCR rate, and apCR rate to neoadjuvant treatment in HR-positive patients having HER2-positive breast cancer, but not in HR-negative patients.